Quantum computational logic with mixed states - Freytes Solari, Hector Carlos (2013)
In this paper we solve the problem how to axiomatize a system of quantum computational gates known as the Poincaré irreversible quantum computational system. A Hilbert-style calculus is introduced obtaining a strong completeness theorem.